Serum miRNAs panel (miR-16-2, miR-195, miR-2861, miR-497) as novel non-invasive biomarkers for detection of cervical cancer - Zhang, Yujuan; Zhang, Donghong; Wang, Fei; Xu, Danfei; Guo, Ye; Cui, Wei (Scientific reports, 2015)
miRNAs have been established as critical layer of regulation during tumorigenesis; extracellular miRNAs are extraordinarily stable; and, quantitative reverse transcript polymerase chain reaction (qRT-PCR) provides a sensitive platform for quantifying miRNAs with a broad dynamic range. Herein, we aimed to establish a serum miRNA signature for diagnosing cervical cancer (CC). In this study, we recruited a cohort of 184 CC, 186 cervical intraepithelial neoplasia (CIN) patients and 193 healthy control subjects. qRT-PCR was performed with serum samples to screen a pool of 444 miRNAs at the initial phase, 66 miRNAs at the training phase and 7 miRNAs at the validation phase. The profile of 4 circulating miRNAs (miR-16-2*, miR-195, miR-2861, miR-497) was established for CC diagnosis. By Receiver Operating Characteristic (ROC) curve analysis, this 4-miRNA signature showed high accuracy in discriminating CC (AUC = 0.849) and CIN individuals (AUC = 0.734) from healthy controls. Among these 4 miRNAs, only miR-16-2*, but not miR-195, miR-2861 or miR497, shared a similar pattern in sera of breast cancer and ovarian cancer patients. Overall, our studies have identified a novel noninvasive biomarker constituted with a panel of four miRNAs (miR-16-2*, miR-195, miR-2861, miR-497).